Piracetam-induced neuroprotection in lipopolysaccharides-challenged EOC-20 cells and mouse brain via attenuating oxidative stress - Vasudevan Mani (Universidade de São Paulo, 2023)
Abstract Therapeutically, piracetam has been used for decades as a cognitive enhancer for memory- related neuronal disorders. The present study aimed to investigate the neuroprotective potential of piracetam on lipopolysaccharides (LPS)-induced neuronal deficit using both in-vitro and in-vivo experimental models. For the in-vitro analysis, EOC-20 murine microglial cells were induced with a neuronal toxicity of 100 µg/ml of LPS, and the formation of intracellular reactive oxygen species (ROS) and nitric oxide (NO) productions were determined. For in-vivo neuroprotective analysis, groups of mice were treated orally with two doses of piracetam (200 and 400 mg/kg) for 30 days. Neuronal toxicity was induced by four intraperitoneal injections of LPS (250 µg/kg/day). The malondialdehyde (MDA) level was measured for oxidative stress, and catalase reduced glutathione (GSH), glutathione reductase (GRD), and superoxide dismutase (SOD) levels were determined as the antioxidant parameters. The result of the cell viability study was that pre-treatment with piracetam significantly protected the LPS-induced cell loss, and attenuated the ROS generation and NO production in LPS-induced EOC-20 cells. Moreover, the treatment of piracetam significantly reduced the MDA levels and improved catalase, GSH, GRD, and SOD activities in LPS-induced mice brains. The overall results from this study supported the neuroprotective effects of piracetam against LPS-induced neuronal toxicity.